Fasilitasi Edukasi "Ibu Cerdas, Keluarga Sehat" Fasilitasi Mengamankan Keuangan Keluarga dari Risiko Biaya Sakit melalui Pemanfaatan Jaminan Kesehatan Nasional : Education Facilitation Program “Ibu Cerdas Keluarga Sehat” Protect Family Finances from the Risk of Medical Costs through the Use of the National Health Insurance Scheme - Rofi’atun Zakiah; Muhammad Zulfikri Mukarom; Yulia Khoerunnisa (Jurnal Pengabdian Masyarakat Saga Komunitas, 2025)
Background: High out-of-pocket (OOP) health expenditures and the persistent gap between health insurance coverage and utilization in rural communities continue to threaten household financial stability. Limited public understanding of self-enrolled membership in Indonesia’s National Health Insurance (JKN) contributes to low administrative independence and suboptimal use of health insurance benefits. This community engagement program aimed to improve community literacy regarding self-enrolled JKN membership through an educational facilitation approach. Methods: The program involved 30 housewives in Kampung Babakan, Petir Village, Bogor, Indonesia. A participatory and interactive educational facilitation method was implemented using a pocket guide containing practical information on self-enrolled JKN membership, including registration procedures, account activation, and membership status verification. Results: The educational intervention resulted in substantial improvements in participants’ knowledge and practical skills related to JKN membership. Following the program, all participants (100%) successfully activated their JKN Mobile accounts and independently verified their membership status, demonstrating enhanced administrative capability in accessing JKN services. Conclusion: Educational facilitation using practical learning materials effectively strengthened community literacy and administrative self-reliance regarding self-enrolled JKN membership. The program also helped reshape participants’ perceptions of JKN as a “health savings” mechanism that provides financial protection against healthcare costs, thereby supporting the sustainability of Universal Health Coverage (UHC) at the community level.